2016
DOI: 10.1002/cncr.30105
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in surgical and adjuvant radiation therapies among women diagnosed with ductal carcinoma in situ

Abstract: BACKGROUND The use of surgery and radiation therapy in treating ductal carcinoma in situ (DCIS) is directed by treatment guidelines and evidence from research. We sought to investigate recent patterns in DCIS treatment by demographic factors. METHODS Data for women diagnosed with DCIS between 1998 and 2011 (n = 416,232) in the National Cancer Data Base were assessed for trends in treatment patterns by age group, calendar year, ancestral/ethnic group and geographic region. The likelihood of receiving specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
4
23
1
Order By: Relevance
“…As survival rates for breast cancer continue to improve, more patients will be living longer after being diagnosed and treated for breast cancer. Moreover, use of mastectomy for breast cancer treatment has also risen over the past decade (2, 3). Along with this increase, more women have been opting for prophylactic mastectomy and breast reconstruction than ever before (2, 4–6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As survival rates for breast cancer continue to improve, more patients will be living longer after being diagnosed and treated for breast cancer. Moreover, use of mastectomy for breast cancer treatment has also risen over the past decade (2, 3). Along with this increase, more women have been opting for prophylactic mastectomy and breast reconstruction than ever before (2, 4–6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, use of mastectomy for breast cancer treatment has also risen over the past decade (2, 3). Along with this increase, more women have been opting for prophylactic mastectomy and breast reconstruction than ever before (2, 4–6). However, despite these trends, older women are still less likely to receive reconstruction following mastectomy, compared with younger patients (711).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, breast‐conserving surgery (BCS), with or without radiotherapy, is considered to be the optimal treatment and equivalent to mastectomy in terms of overall survival . At present, approximately 30% of DCIS patients are treated with mastectomy, 40% with BCS combined with radiotherapy and 30% with excision alone . While BCS without radiotherapy is potentially an option for treatment of low‐risk DCIS, adjuvant radiotherapy for DCIS patients treated with BCS is considered standard therapy and no groups have been identified that do not benefit, in terms of reduction in local recurrence (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…While BCS without radiotherapy is potentially an option for treatment of low‐risk DCIS, adjuvant radiotherapy for DCIS patients treated with BCS is considered standard therapy and no groups have been identified that do not benefit, in terms of reduction in local recurrence (Table ). Data from the National Cancer Data Base, including 416 232 DCIS patients from 1998 to 2011, show that approximately 70% of patients received radiotherapy after BCS, with different trends within various age groups, ethnicities and geographical distribution . Generally, radiotherapy is recommended to patients with high‐risk DCIS based on certain features, including large‐sized lesions (15 mm and more), intermediate to high cytonuclear grade and presence of comedo‐type necrosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Patient choice is also a contributing factor as evidenced by the NHS Breast Screening Programme where patient choice accounts for about 11% of mastectomies for DCIS . Recently, in the UK and United States, the rate of mastectomy has increased particularly in young women perceived at high risk of further breast cancer events . In a report on 8000 DCIS cases included in the Sloane Project and treated between 2003 and 2012 the rate of attempted BCS was 79% and successful BCS was 68% .…”
Section: Discussionmentioning
confidence: 99%